The Effects of Goal Setting and Self-Instruction Training on the Performance of Unionized Employees - Brown, Travor; Latham, Gary (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2000)
This study assesses the effectiveness of goal setting, goal setting plus training in self-instruction, and being urged to do one's best on the performance of unionized employees (n = 32). The ability of managers, peers and self to observe changes in employee performance was also assessed. Appraisals were made prior to and 10 weeks following three interventions. ANCOVA indicated that employees who set specific, difficult goals had significantly higher performance than those in the doing one's best and those doing goal setting plus self-instruction. Moreover, self-efficacy correlated positively with subsequent performance. Employee satisfaction with the performance appraisal process was high across the three conditions. Peers provided better data for assessing the effect of an intervention than self or managers.